Mendeteksi Pengaruh Persepsi Mahasiswa Terhadap Vaksinasi Covid-19 Menggunakan Ordinal Logistic Regression - Muhammad Marizal; Afifa Nurmita (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
The COVID-19 vaccine is one of the government's breakthroughs to fight and deal with the COVID-19 pandemic. Meanwhile, students' perceptions of vaccines are important to know. The reason is that many students from various universities, especially those from UIN Suska Riau, have their own opinions or opinions about the vaccination. So by using the Ordinal Logistic Regression obtained in this study, it is possible to estimate the categories of students' perceptions of vaccines with the independent variable being knowledge and information about COVID-19 vaccination